Children's mental health in times of a COVID-19 pandemic: integrative review (Research, Society and Development, 2021)
Objective: Conduct a survey in the scientific literature of the impacts of COVID-19 on children's mental health. Methodology: This is an integrative review carried out based on searches in the scientific databases Scopus, PubMed, Embase and Medline. Original research articles, open access and published between 2020 and 2021 were included. For the search key, the descriptors “Coronavirus Infections”, “Child Health”, “Child Preschool” and “Mental Health” and synonyms in English were used. 280 studies were found, 6 of which were included. Results: All selected studies indicated evidence level V and found different negative impacts that the COVID-19 pandemic caused on the mental health of children, affecting their actions, thoughts and emotions. Conclusion: In view of the implications caused by the pandemic on the mental health of children, it is important to adopt measures that can keep them healthy, such as the practice of physical activities inside their own homes, games that do not involve the use of screens and performance of family meals.